2013
DOI: 10.1007/s10680-013-9300-y
|View full text |Cite
|
Sign up to set email alerts
|

Applying Relational Models to the Graduation of Disability Schedules

Abstract: Age-specific rates of particular disability types are important for planning purposes and are a valuable input to estimates of populations with different disabilities. However, survey estimates of schedules of disability rates for the constituent countries of the UK display evidence of sampling variability and sub-national disability schedules are either extremely unreliable as a result of small sample sizes or are unavailable for reasons of disclosure protection. This paper develops and evaluates a method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, health is a stock variable sensitive to past experience (Barendregt et al 1997;Brouard/Robine 1992;Murray et al 2002) and with a complex interaction between health and mortality, making it diffi cult to accurately model age-specifi c health prevalence (Riffe et al 2016(Riffe et al , 2017. In this regard, it has been shown that some relational models provide a good fi t for modelling some types of disabilities by age (Marshall et al 2013), while alternative summary measures that incorporate the mortality history of cohorts and therefore combine health and mortality information have also been proposed (Sauerberg et al 2020). However, these methods are more important to capture the relationship between age-specifi c prevalence of disability and various disability types rather than to harmonise and extrapolate prevalence at older ages.…”
Section: Figurementioning
confidence: 99%
“…In addition, health is a stock variable sensitive to past experience (Barendregt et al 1997;Brouard/Robine 1992;Murray et al 2002) and with a complex interaction between health and mortality, making it diffi cult to accurately model age-specifi c health prevalence (Riffe et al 2016(Riffe et al , 2017. In this regard, it has been shown that some relational models provide a good fi t for modelling some types of disabilities by age (Marshall et al 2013), while alternative summary measures that incorporate the mortality history of cohorts and therefore combine health and mortality information have also been proposed (Sauerberg et al 2020). However, these methods are more important to capture the relationship between age-specifi c prevalence of disability and various disability types rather than to harmonise and extrapolate prevalence at older ages.…”
Section: Figurementioning
confidence: 99%